Helminthological screening of free-ranging grey brocket deer Mazama gouazoubira Fischer, 1817 (Cervidae: Odocoileini) from Brazilian Pantanal wetlands, with considerations on Pygarginema verrucosa (Molin, 1860) Kadenatzii, 1948 (Spirocercidae: Ascaropsinae) Avaliação helmintológica de veados-catingueiros Mazama gouazoubira Fischer, 1817 (Cervidae: Odocoileini) de vida livre, procedentes do Pantanal brasileiro, com considerações sobre Pygarginema verrucosa (Molin, 1860) Kadenatzii, 1948 (Spirocercidae: Ascaropsinae) - EG. Lux Hoppe (Brazilian Journal of Biology, 2010)
The Brazilian Pantanal wetlands are a unique ecosystem with a faunistic composition similar to that of the adjacent biomes but in higher densities. The early establishment of domestic cattle husbandry in that area introduced pathogens that may influence the indigenous Pantanalian fauna. In this paper, the authors describe the helminthfauna of ten free-ranging adult Mazama gouazoubira from the Paiaguás sub-region, along with the descriptors of infection. Morphological description of Pygarginema verrucosa is supplied, with comments on other species of this genus. The helminth species found are similar to domestic cattle helminthfauna of the same physiographic region, suggesting an adaptation of bovine parasites to this host. O Pantanal brasileiro é um ecossistema único, com composição faunística semelhante à dos biomas adjacentes, mas com densidades superiores. O gado introduzido na região pode ter carreado patógenos nesse ecossistema que podem, de alguma forma, influenciar a fauna local. Neste artigo, é descrita a helmintofauna de dez indivíduos adultos de Mazama gouazoubira provenientes da sub-região de Paiaguás, juntamente com os indicadores de infecção helmíntica. Ainda, são fornecidas informações sobre a morfologia de Pygarginema verrucosa, com comentários sobre outras espécies deste gênero. As espécies de helmintos diagnosticadas são semelhantes àquelas encontradas em bovinos da mesma região, sugerindo adaptação destas no hospedeiro estudado.